The business of resort management - Murphy, Peter E. (Amsterdam, 2008)
Based on an analysis of global resort opportunities and trends, the book focuses on those generic features that differentiate regional resort management from urban-centric management needs and priorities. Using international comparative case studies from spas in Belgium and Butlins in the UK, to the Gold Coast, Australia and Las Vegas, USA, Murphy presents best case/benchmark examples of a range of resorts to illustrate what can be achieved
Keywords: Resort- Management